Analysis of an operational trans-conductance amplifier with positive feedback - Park, Sung Sik (International Journal of Electrical and Computer Engineering (IJECE), 2024)
In this paper, we present an analysis of an operational trans-conductance amplifier (OTA) with two positive feedback. The direct current (DC) transfer function is obtained by analyzing the OTA using the drain current in the weak inversion region. The analysis results were verified through comparison with SPICE simulations, and the characteristics of the DC transfer function analysis for the OTA design are well matched with the simulation results. The designed OTA dissipates a low power of 41.4 nW, and features the slew rate is improved by 436% compared to a conventional OTA without two positive feedback. Additionally, a DC gain and a unity-gain bandwidth is improved by 36 dB and 6.7 times, respectively. The OTAs are designed for the 0.18 μm complementary metal–oxide–semiconductor (CMOS) process.